Artificial Intelligence Powered Chatbot for Business - Effah Abdullah Kadasah (International Journal of Information Technology and Business, 2023)
Text has become an essential interaction manner between people. The use of chatbots improved quickly in business area including marketing, customer service and e-commerce. Users value chatbots because they are fast, intuitive and convenient. This paper discussed about the artificial intelligence technology that used to develop and implement chatbots which can the organization used to benefit in their businesses. A chatbot is a computer program that can interact with a human by using natural language. The main three areas in business that using chatbot the most are marketing, customer service and e-commerce fields. The roles of chatbot in mentioned areas has been discussed in this paper. AI powered chatbots transform business by reducing costs, increasing revenue and enhancing the customer experience. The benefits and limitation of chatbots have been also discussed in this paper.